Foliar application of zinc oxide nanoparticles: An effective strategy to mitigate drought stress in cucumber seedling by modulating antioxidant defense system and osmolytes accumulation. (February 2022) - Ghani, Muhammad Imran; Saleem, Sana; Rather, Shabir A.; Rehmani, Muhammad Saad; Alamri, Saud; Rajput, Vishnu D.; Kalaji, Hazem M.; Saleem, Noor; Sial, Tanveer Ali; Liu, Mengyun
Abstract: Drought is a major environmental threat that affects plant growth and productivity. Strategies to mitigate the detrimental impacts of drought stress on plants are under scrutiny. Nanotechnology is considered an effective tool in resolving a wide range of environmental issues by offering novel and pragmatic solutions. A pot experiment was performed to determine the efficacy of zinc oxide nanoparticles (ZnO NPs) as a foliar application (25 mg L −1 and 100 mg L −1 ) on the growth performance of cucumber subjected to drought stress. Applied ZnO NPs under normal conditions resulted in significant growth and biomass enhancement while reducing drought-induced decline. Photosynthetic pigments, photosynthesis, and PSII activity enhanced due to ZnO NPs application, attaining maximal values at 100 mg L −1 of ZnO NPs. Drought stress restricted growth and biomass buildup in cucumber seedlings by stimulating oxidative stress, which was manifested to excessive buildup of reactive oxygen species (ROS) and peroxidation, thereby decreasing membrane functioning. Plants exposed to ZnO NPs exhibited a reduction in ROS accumulation and lipid peroxidation. The substantial reduction in oxidative damage was manifested with the enhancement of enzymatic and non-enzymatic antioxidant components. The phenol and mineral contents were reduced due to drought stress. In addition, the content of proline, glycine betaine, free amino acids, and sugars increased due to ZnO NPs under normal and drought conditions. Furthermore, the drought-induced decline in the content of phenol and mineral nutrients was mitigated by ZnO NPs foliar application. These findings reveal that exogenous ZnO NPs application may be a pragmatic option in dealing with the drought stress of cucumber seedlings. Graphical abstract: Image 1 Highlights: Drought stress severely affects plant growth. The use of ZnO NPs is a promising strategy to mitigate drought stress. ZnO NPs show increased antioxidant defense system, nutrient absorption, and osmolytes accumulation in cucumber seedlings. Reduction in ROS, lipid peroxidation is observed in ZnO NPs treated seedlings.